2022
DOI: 10.7189/jogh.12.11001
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean delivery on maternal request and common child health outcomes: A prospective cohort study in China

Abstract: Background Cesarean delivery vs vaginal delivery was reported to increase the risks of childhood obesity, pneumonia, anemia, and neurobehavioral disorders, but few studies were able to deal with the confounding biases associated with medical conditions indicating cesareans. This prospective cohort study aims to investigate the associations of non-medically indicated cesarean delivery on maternal request (CDMR) with these child health outcomes. Methods Among 17 748 liveb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Most studies on pregnancy complications have focused on mode of delivery and gestational diabetes. Within 14 51,52,61,[75][76][77][78][79][80][81][82][83][84][85] out of 22 studied populations, caesarean section (CS) was identified as a risk factor for increased childhood obesity. 7 observational studies 11,38,66,77,[86][87][88] and 1 RCT 89 reported no association between CS and childhood obesity.…”
Section: Risk Factors For Childhood Obesity During Pregnancymentioning
confidence: 99%
“…Most studies on pregnancy complications have focused on mode of delivery and gestational diabetes. Within 14 51,52,61,[75][76][77][78][79][80][81][82][83][84][85] out of 22 studied populations, caesarean section (CS) was identified as a risk factor for increased childhood obesity. 7 observational studies 11,38,66,77,[86][87][88] and 1 RCT 89 reported no association between CS and childhood obesity.…”
Section: Risk Factors For Childhood Obesity During Pregnancymentioning
confidence: 99%
“…Despite diabetes treatment advances, outcomes are usually unsatisfactory, highlighting the need for further research and intervention. Neonatal outcomes are affected by maternal diabetes [7,8]. Fetal hyperinsulinemia, macrosomia, and delivery problems may result from high maternal blood glucose [9,10].…”
Section: Introductionmentioning
confidence: 99%